Moral Character of Society in the Qur’an on the Story of Ashab Al-Sabti - Febriansyah Febriansyah; Septiawadi Kari Mukmin; Beko Hendro (Jurnal Semiotika Quran, 2024)
This research is motivated by the existence of moral degradation caused by films, stories, and news in society that encompass various aspects of moral decline, such as issues of collusion, corruption, and nepotism (KKN), the deviation of virtuous values, and the lack of empathy and social responsibility. If films, stories, and news can shape a person's character, then the Qur'an can certainly improve one's behavior. The story of Ashab Al-Sabti was chosen for this study because it contains three groups: the pious advisors, those who remain passive in the face of wrongdoing, and those who transgress and are disobedient. This research aims to examine the moral characteristics of these three groups. Through the approach of exegesis and sociology, the characters within this story can be analyzed. Therefore, this research uses a qualitative method with library research and descriptive analysis as the data analysis technique. The results of the study show that the character analysis of these three groups is divided into two categories: positive characteristics, which include social concern, obedience, loyalty, and perseverance, and negative characteristics, which include despair and rebellion. Efforts to contextualize the moral character in the phenomenon of KKN conclude that emphasizing the role of the passive group in society's structure can potentially lead to moral decay and social disorder. This occurs because individuals remain silent in the face of falsehood, causing the truth to become less dominant. This serves as a lesson for society that in order to form a civil society, there needs to be action and socialization in conveying the truth.